Visceral Adiposity Index as a Tool for Cardiometabolic Risk in Obese Older Women - Ayanne Rodrigues Cambiriba; Daniel Vicentini de Oliveira; Pablo Valdes-Badilla; Marcelo Picinin Bernuci; Sônia Maria Marques Gomes Bertoloni; Bráulio Henrique Magnani Branco (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVE: To correlate anthropometric measurements, lipid profile, cardiorespiratory fitness, and visceral adiposity index (VAI) in sedentary obese older women. METHODS: Twenty-seven insufficiently active and overweight older women were included in this cross-sectional study. We evaluated their anthropometric profile (body weight and stature, body mass index, waist and hip circumferences) and body composition (fat mass, body fat percentage, and musculoskeletal mass). Venous blood samples were analyzed for high and low-density lipoproteins (HDL-c and LDL-c), triglycerides (TG), and the LDL/HDL ratio. Peak oxygen uptake (VO2 peak) was measured using an adapted Bruce test using direct spirometry. We tested data normality and applied Pearson's correlation, assuming a p ≤ 0.05. RESULS: The following correlations were observed: VAI and HDL (r = -0.53); VAI and LDL (r = 0.35); VAI and TG (r = 0.86); VAI and TG/HDL (r = 0.99) and VAI and VO2 peak (r = -0.55), with p < 0.01 for all analyses. CONCLUSION: The findings suggested that VAI may be used as a tool to assess cardiometabolic risk in obese older women. Future studies should evaluate the applicability of VAI as a cardiometabolic risk factor indicator in older adults.